Enhanced partial transmit sequence technique with improved partitioning and phase factor methods for orthogonal frequency division multiplexing systems - Ibraheem, Zeyid Tariq (School of Computer and Communications Engineering, 2016)
The goal of this thesis is to analyze the peak-to-average power ratio (PAPR) of the transmitted signals in OFDM systems. A new family of PAPR reduction methods based on PTS techniques is developed that can achieve minimum PAPR of the OFDM transmitted signal and reduce the computational complexity simultaneously. The performance is evaluated through numerical computations and simulations of OFDM systems. In this thesis, the implementation of the proposed techniques at the transmitter is considered. Performance of PAPR reduction and computational overhead/complexity are considered in the scope of this thesis.